Factors Related to Fruit Vegetable Consumption of Adolescent in Rural and Urban Areas - Fayasari, Adhila; Amelia, Chika Meidiana; Wijayanti, Tri Sari (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Vegetables and fruit consumption contain many benefits. Even though, in Indonesia consumption of vegetables and fruit still less than a recommendation, especially in adolescent. The purpose of this research is to identify the factors affecting the consumption of fruit vegetables consumption (FV) adolescents in urban area (Jakarta) and Rural (Bogor). This research used cross-sectional design in 213 junior high school student in Jakarta and Bogor from January- Februari 2020. Knowledge, self-efficacy, parental influence and availability fruit vegetable were collected by self-questionnaire, and consumption of fruit and vegetable were collected by SQ-FFQ. Data were analysed using chi-square test. Low vegetables and fruit consumption were 24.3% and 13,2%, in urban and rural, respectively. There were significant relationship between self -efficacy (p 0.034; OR 2,61), availability vegetables and fruit (p 0.048; OR 0,41), parental influence (p 0.032; OR 2,95), in urban but, there was no significant relationship between all factors to FV consumption